2017
DOI: 10.1039/c7ra09225c
|View full text |Cite
|
Sign up to set email alerts
|

Changes in degrading ability, populations and metabolism of microbes in activated sludge in the treatment of phenol wastewater

Abstract: With an increase in phenol concentration, biodegradable soluble microbial by-product-like matter in sludge EPS is gradually replaced by non-biodegradable tryptophan protein-like matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 50 publications
2
10
0
1
Order By: Relevance
“…The high concentration of phenolic compounds inhibits the growth and activity of plants and microorganisms. 36,37 The 4-CP removal rate was 36.5% at stage 3, which was lower than in stage 2, due to the decreased removal efficiency of Cr( vi ) and TCr, and the negative effects caused by the high concentration of 4-CP. The COD removal rate at stage 2 (59.6%) was slightly higher than at stage 1 (55.1%) and stage 3 (52.9%), which may be attributed to the low concentration of phenolic compound stimulating the growth of plants and microorganisms to promote electricity generation and the degradation of organic matter.…”
Section: Resultsmentioning
confidence: 98%
“…The high concentration of phenolic compounds inhibits the growth and activity of plants and microorganisms. 36,37 The 4-CP removal rate was 36.5% at stage 3, which was lower than in stage 2, due to the decreased removal efficiency of Cr( vi ) and TCr, and the negative effects caused by the high concentration of 4-CP. The COD removal rate at stage 2 (59.6%) was slightly higher than at stage 1 (55.1%) and stage 3 (52.9%), which may be attributed to the low concentration of phenolic compound stimulating the growth of plants and microorganisms to promote electricity generation and the degradation of organic matter.…”
Section: Resultsmentioning
confidence: 98%
“…The result of this study demonstrated the eminent role of Betaproteobacteria in aromatic biodegradation, in which a majority of the clones recovered from both the aerial and microbial recycle tanks belong to this class. A study by Chen et al (2017) showed that Proteobacteria dominated the wastewater sludge bacterial community and their relative abundance increased to around 80% of the total population when the sludge was adapted to 350 mg/L phenol, despite that further classification of the phylum was not described in detail. Silva et al (2012) also reported that several genus belonging to Betaproteobacteria, including Diaphorobacter, Thauera, and Comamonas, were found in abundance in petroleum wastewater refineries enriched with phenol.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Figure 3 and Figure 4 showed the four contour plots of R-square statistic for regression analysis. As shown in this figure, horizontal and vertical lines were drawn to divide the EEM into five regions [28,43]. For Furthermore, the R-square statistic between fluorescence intensities of EEM data and measured DOC concentration was analyzed directly to estimate the effectiveness of pre-processing results as indicators for DOC concentration.…”
Section: Pre-processingmentioning
confidence: 99%
“…Figures 3 and 4 showed the four contour plots of R-square statistic for regression analysis. As shown in this figure, horizontal and vertical lines were drawn to divide the EEM into five regions [28,43]. For EEM Region I and Region II, which are related to tyrosine protein-like matter, the emission wavelengths are shorter than 350 nm and excitation wavelengths are shorter than 250 nm.…”
Section: Pre-processingmentioning
confidence: 99%